The US-China Trade War and the Relocation of Global Value Chains to Mexico - Hâle Utar; Alfonso Cebreros Zurita; Luis Bernardo Torres Ruiz; Hale Utar (Center for Economic Studies and ifo Institute (CESifo), 2023)
Did the 2018/19 US-China trade war trigger adjustment of Global Value Chains (GVCs) and nearshoring to Mexico? We address this question with confidential longitudinal firm-level trade data from Mexico that covers the universe of international trade transactions over 2015-2021. By merging the firm-level customs data with a registry of GVC firms and constructing firm-level measures of trade policy exposures based on firms' pre-shock trade at the level of HS 6-digit products-destination pairs, we show that increased Chinese import protection in the US has a significant positive impact on Mexican firms' trade with the US, and this positive impact is entirely driven by GVC firms, and especially those in skill-intensive manufacturing industries. The nature of the impact of the heightened Chinese import tariffs on GVC firms' sourcing suggests a rise in GVC activities in Mexico with linkages to Asian and US-based GVCs. Our analysis also reveals increased net exports and product offerings of Mexican GVC firms in response to the heightened Chinese import protection in the US, suggesting increased domestic activities in Mexico. However, we also document a negative impact of the retaliatory tariffs of China, primarily affecting export services and a counterbalancing negative effect of the US tariffs via GVC firms' inputs from China, highlighting the complex dynamics at play. Overall, our findings show a reorganization of GVCs towards Mexico as a consequence of the trade war and provide evidence for the role of trade policy in reshaping GVCs.
Keywords: F13; F14; F23; F61; F68; 330; trade war; GVCs; nearshoring; Mexico; US; China